Assessment on the applicability of finite difference methods to model light propagation in photonic liquid crystal fibers - Rutkowska, Katarzyna Agnieszka; Wei, Li-Wei (Photonics Letters of Poland, 2012)
In this report we show our numerical scheme based on a finite difference approach and devoted to model light propagation in photonic liquid crystal fibers. Our method allows for an optical anisotropy of liquid crystals to be included in calculations. In particular, a vector-field mode solver implemented here allows an arbitrary rotation of LC molecules in the transverse plane with respect to the propagation axis to be considered. To this end, suitable analytical formulations have been derived and numerically implemented. Computational scheme developed has been optimized and checked for numerical convergence. Obtained results have been validated in accordance to those described in literature or got from commercial software. Qualitative comparison with experimental data obtained for a particular sample of PLCF also has been made. Full Text: PDF References P. St. J. Russell, "Photonic Crystal Fibers", Science 299, 358 (2003). CrossRef T.R. Woliński et al., "Emerging photonic devices based on photonic liquid crystal fibers", Phot. Lett. Poland 3(1), 20 (2011). CrossRef I-C. Khoo, S-T. Wu, Optics and Nonlinear Optics of Liquid Crystals (World Scientific Pub., Singapore 1993). CrossRef J. Schirmer et al., "Birefringence and Refractive Indices Dispersion of Different Liquid Crystalline Structures", Mol. Cryst. Liq. Cryst. 307(1), 17 (1997). CrossRef Z. Zhu, T.G. Brown, "Full-vectorial finite-difference analysis of microstructured optical fibers", Opt. Exp. 10(17), 853 (2002). CrossRef M. Koshiba, K. Saitoh, "Numerical verification of degeneracy in hexagonal photonic crystal fibers", IEEE Phot. Techn. Lett. 13(12), 1313 (2001). CrossRef